Anti‐inflammatory ethosomal nanoformulation in combination with iontophoresis in chronic wound healing: An ex vivo study. Issue 9 (18th October 2021) - Mombeiny, Reza; Tavakol, Shima; Kazemi, Mostafa; Mehdizadeh, Mehdi; Hasanzadeh, Akbar; Karimi Babaahmadi, Mohammad; Abedi, Ali; Keyhanvar, Peyman
Abstract: Prescription of anti‐inflammatory drugs may be considered as a promising strategy in chronic wound healing where the inflammatory disturbance has delayed the healing process. It seems that hydrocortisone 17‐butyrate (HB17) would be promising in the form of a nano‐formulation to enhance drug delivery efficacy. In the present study, transdermal delivery of nano‐HB17 in combination with iontophoresis was investigated ex vivo. Ethosomal‐HB17 was synthesised using lecithin, ethanol and cholesterol with a different ratio by hot method. The negative ethosomal‐HB17 particle size was around 244 ± 4.3 nm with high stability of up to 30 days. Additionally, evaluated entrapment efficiency of HB17 in ethosomes by high performance liquid chromatography was 40.6 ± 2.21%. Moreover, the permeation speed and amount of H17B in complete‐thickness rat skin in the presence and absence of iontophoresis showed that the penetration of free H17B and ethosomal‐H17B formulations were zero and 7.98 μg/cm 2 in 120 min, respectively. Whereas in the case of applying iontophoresis, permeation amount obtained was zero and 19.69 μg/cm 2 in 30 min in free H17B and ethosomal‐H17B formulations, respectively. It has been concluded that transdermal delivery of ethosomal‐H17B is an effective strategy to enhance drug delivery and it will be improved when it is combined with iontophoresis.